Beyond the Horizon: Integrating Immersive Learning Environments in the Everyday Classroom - Dengel, Andreas; Buchner, Josef; Mulders, Miriam; Pirker, Johanna (2021 7th International Conference of the Immersive Learning Research Network (iLRN), 2021)
As Immersive Learning research gains traction, questions arise about how educational Virtual and Augmented Realities can be transferred from laboratory settings and pilot projects into everyday teaching. This paper analyzes existing pedagogical frameworks to identify influencing factors and challenges relevant to teaching and learning with immersive learning environments. We distinguish Immersive Learning as individual learning processes supported by immersive technology and Immersive Teaching as the process of teaching with immersive technology. We subsume learner-specific influences (micro-level), teacher- and classroom-specific influences (meso-level) and institutional and governmental factors (macro-level) for Immersive Teaching and Learning. We conclude that, while investigating isolated variables is important for basic research, efforts integrating Virtual and Augmented Reality in everyday classrooms raise new challenges and questions for future research on the complex relationship between various factors.